The Clamping of End-Tidal Carbon Dioxide Does Not Influence Cognitive Function Performance During Moderate Hyperthermia With or Without Skin Temperature Manipulation - Schultz Martins, Ricardo; Wallace, Phillip J.; Steele, Scott W.; Scott, Jake S.; Taber, Michael J.; Hartley, Geoffrey L.; Cheung, Stephen S. (Frontiers in Psychology, 2021)
Increases in body temperature from heat stress (i.e., hyperthermia) generally impairs cognitive function across a range of domains and complexities, but the relative contribution from skin versus core temperature changes remains unclear. Hyperthermia also elicits a hyperventilatory response that decreases the partial pressure of end-tidal carbon dioxide (PetCO2) and subsequently cerebral blood flow that may influence cognitive function. We studied the role of skin and core temperature along with PetCO2 on cognitive function across a range of domains. Eleven males completed a randomized, single-blinded protocol consisting of poikilocapnia (POIKI, no PetCO2 control) or isocapnia (ISO, PetCO2 maintained at baseline levels) during passive heating using a water-perfused suit (water temperature 49°C) while middle cerebral artery velocity (MCAv) was measured continuously as an index of cerebral blood flow. Cognitive testing was completed at baseline, neutral core-hot skin (37.0 ± 0.2°C-37.4 ± 0.3°C), hot core-hot skin (38.6 ± 0.3°C-38.7 ± 0.2°C), and hot core-cooled skin (38.5 ± 0.3°C-34.7 ± 0.6°C). The cognitive test battery consisted of a detection task (psychomotor processing), 2-back task (working memory), set-shifting and Groton Maze Learning Task (executive function). At hot core-hot skin, poikilocapnia led to significant (both p < 0.05) decreases in PetCO2 (∆−21%) and MCAv (∆−26%) from baseline, while isocapnia clamped PetCO2 (∆ + 4% from baseline) leading to a significantly (p = 0.023) higher MCAv (∆−18% from baseline) compared to poikilocapnia. There were no significant differences in errors made on any task (all p > 0.05) irrespective of skin temperature or PetCO2 manipulation. We conclude that neither skin temperature nor PetCO2 maintenance significantly alter cognitive function during passive hyperthermia.